Global Analysis of HuR-Regulated Gene Expression in Colon Cancer Systems of Reducing Complexity - López de Silanes, Isabel (Gene Expr, 2018)
HuR, a protein that binds to target mRNAs and can enhance their stability and translation, is increasingly recognized as a pivotal regulator of gene expression during cell division and tumorigenesis. We sought to identify collections of HuR-regulated mRNAs in colon cancer cells by systematic, cDNA array-based assessment of gene expression in three systems of varying complexity. First, comparison of gene expression profiles among tumors with different HuR abundance revealed highly divergent gene expression patterns, and virtually no changes in previously reported HuR target mRNAs. Assessment of gene expression patterns in a second system of reduced complexity, cultured colon cancer cells expressing different HuR levels, rendered more conserved sets of HuR-regulated mRNAs. However, the definitive identification of direct HuR target mRNAs required a third system of still lower complexity, wherein HuR–RNA complexes immunoprecipitated from colon cancer cells were subject to cDNA array hybridization to elucidate the endogenous HuR-bound mRNAs. Comparison of the transcript sets identified in each system revealed a strikingly limited overlap in HuR-regulated mRNAs. The data derived from this systematic analysis of HuR-regulated genes highlight the value of low-complexity, biochemical characterization of protein–RNA interactions. More importantly, however, the data underscore the broad usefulness of integrated approaches comprising systems of low complexity (protein–nucleic acid) and high complexity (cells, tumors) to comprehensively elucidate the gene regulatory events that underlie biological processes.